DETERMINASI CESIUM-137 DARI AIR LAUT MENGGUNAKAN RESIN HEKSASIANOFERAT - Murdahayu Makmur; Heru Umbara (Widyariset, 2009)
Determination of cesium-137 in seawater was done using the hexacyanoferrate resin as ion exchanger from 3 point samplings of surface seawater. The hexacyanoferrate ion exchanger matrix was prepared by performing the reaction ofsilica gel supported with potassium hexacyanoferrate and copper (II) chloride. In order to test the performance of the ion exchanger, a batch experiment was performed. A known activity of cesium-137 was used to spike seawater then the hexacyanoferrate resin was added. The separated hexacyanoferrate resin was then counted with gamma spectrometer The cesium-I 37 concentration used in the work varies between 0.5 Bq-20 Bq while the results of the adsorbing efficiency varies between 58-96%. In time variation between 0.5-20 minutes, the adsorbing efficiency varies between 77-96% with highest efficiency at contact time 60 minutes. The hexacyanoferrate ion exchange columns were used to process the Jepara's seawater The calculated cesium-137 activities were 1.37 Bq/m3-2.76 Bq/m3.